Relokasi Permukiman Warga Bantaran Sungai Ciliwung di Provinsi Jakarta - Nur Aini Fitrianti; Nurul Laili Fadhilah (Lentera Hukum, 2018)
As the population grows rapidly, more and more illegal settlements are built on state land that prohibits shelter, specifically in the Ciliwung River area. The Jakarta Provincial Government has a policy to relocate the residents of Ciliwung River, to ensure that the river and Ciliwung river functions return to normal. The government provides for relocation and the construction of flats, so residents may have increased wellbeing. We explore whether the relocation of Ciliwung River residents is in accordance with Law No. 2 of 2012, on Land Procurement for the Public Interest and Regional Regulation of the Special Capital Province of Jakarta No. 1 of 2012 on Spatial Plans. Normative juridical research concludes that the relocation of the settlement is in accordance with Law No. 2 of 2012 on Land Procurement for the Public Interest and Regional Regulation of the Province of Jakarta Capital Special Region No. 1 of 2012 on Spatial Planning. Keywords: Local Government, Relocation, River Basin Settlements